2011
DOI: 10.5268/iw-1.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxin production in seven Ethiopian Rift Valley Lakes

Abstract: We hypothesized that unusual deaths and illnesses in wild and domestic animals in lake areas of the Rift Valley south of Addis Ababa were caused by toxic cyanobacteria. In the first cyanotoxic analyses conducted in samples from Ethiopia, we found lakes Chamo, Abaya, Awassa, Chitu, Langano, Ziway, and Koka all had concentrations of microcystins (MC) ranging from trace to hazardous, whereas only traces less than limits of detection (LOD) of cylindrospermopsin (CYN) were found. In the December 2006 dry season we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Lakes Hawassa, Ziway and Koka are situated in the Ethiopian rift valley ( Figure 1) and are nearby to each other with similar landscape setting, land use and altitude (Willén et al, 2011). Lake Hawassa is relatively small and deep, lakes Ziway and Koka are large and shallow ( Figure 1).…”
Section: Studymentioning
confidence: 99%
“…Lakes Hawassa, Ziway and Koka are situated in the Ethiopian rift valley ( Figure 1) and are nearby to each other with similar landscape setting, land use and altitude (Willén et al, 2011). Lake Hawassa is relatively small and deep, lakes Ziway and Koka are large and shallow ( Figure 1).…”
Section: Studymentioning
confidence: 99%
“…Cyanobacteria are widely distributed and can form dense blooms in lakes and reservoirs in both temperate, subtropical, and tropical regions (Willén et al 2011). Many species of cyanobacteria produce toxic compounds, which have been shown to cause serious blooms of cyanobacteria may be the consequence of aquaculture production, since fish excreta and unassimilated feed can introduce eutrophic or hypereutrophic conditions into intensively operated fish farms (Smith et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, microcystins appear to contribute to more than 90% of the cyanotoxins detected in northern and middle European waters (Spoof et al 2010), and microcystins also appear to be dominant toxins in many other parts of the world (Willén et al 2011, Sant'Anna et al 2008. Microcystins consist of 3 dominant toxin variants: the arginine-containing microcystins (MC)-RR, MC-YR, and MC-LR, with different degrees of methylation (Spoof et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the death of wildlife, in the study area, was due to toxic Microcystis. Willen et al (2011) studied the deaths of wild and domestic animals around the Rift Valley in Kenya and reported traces of microcystins produced by Microcystis aeruginosa as the dominant species. The toxins were found to exceed 1 µg L -1 levels.…”
Section: Introductionmentioning
confidence: 99%